High precision tracking control for a sequence of way-points using dynamic unicycles. Issue 10 (July 2019) - Zuo, Lei; Ma, Wenrui; Yan, Maode; Yang, Panpan
Highlights: A simplified electrical motor is applied into the unicycle's dynamic model in the proposed tracking system. A novel way-point tracking control scheme is proposed for the unicycle in both kinematic and dynamic levels, in which the stability and feasibility are strictly analyzed. Comparing with the general feedback tracking controllers, the proposed tracking algorithm can drive the dynamic unicycle to its target with high precision and the computational efficiency is improved. Abstract: This paper investigates the high precision way-point tracking control problems for dynamic unicycles. Firstly, a simplified electrical motor is used to provide the torques in unicycle's dynamic model. Then, in order to improve the tracking precision, a kinematic controller and a dynamic controller are proposed to drive the unicycle to its given way-points, respectively. A group of parameter conditions is developed for the tracking system to avoid the singularity. Comparing with the other tracking methods, our proposed tracking controllers can effectively drive the dynamic unicycle to its targets with high precision. The stability and performance of proposed tracking method are strictly analyzed in both kinematic and dynamic levels. In final, numerical simulations are provided to verify the effectiveness and advantages of proposed approaches.